2018
DOI: 10.1159/000490196
|View full text |Cite
|
Sign up to set email alerts
|

European Organization for Caries Research Workshop: Methodology for Determination of Potentially Available Fluoride in Toothpastes

Abstract: Toothpastes are the most universally accepted form of fluoride delivery for caries prevention. To provide anti-caries benefits, they must be able to release fluoride during the time of tooth brushing or post brushing into the oral cavity. However, there is no standard accepted procedure to measure how much fluoride in a toothpaste may be (bio) available for release. The European Organization for Caries Research proposed and supported a workshop with experts in fluoride analysis in toothpastes and representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
7

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 34 publications
2
45
0
7
Order By: Relevance
“…However, fluoride must be chemically soluble in any toothpaste formulation to be released in the oral cavity during toothbrushing and to interfere with the physicochemical process of caries, either reducing demineralization of sound enamel-dentine mineral structure or enhancing remineralization of incipient caries lesions [Cury and Tenuta, 2008;Cury and Tenuta, 2009;Cury and Tenuta, 2014]. Based on this premise and the necessity of research to evaluate the relationship between the concentration of soluble fluoride present in toothpaste and the concentration found in saliva during and after brushing [Martinez-Mier et al, 2019], this study was done with Na 2 FPO 3 /Ca-CO 3 -based toothpaste. For this research, the brand of toothpaste was fixed (Table 1) and the variable under study was the concentration of TSF (ion FPO 3 2-+ ion F) in the toothpaste, which was obtained by standardized time of accelerated aging [Tabchoury and Cury, 1994].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, fluoride must be chemically soluble in any toothpaste formulation to be released in the oral cavity during toothbrushing and to interfere with the physicochemical process of caries, either reducing demineralization of sound enamel-dentine mineral structure or enhancing remineralization of incipient caries lesions [Cury and Tenuta, 2008;Cury and Tenuta, 2009;Cury and Tenuta, 2014]. Based on this premise and the necessity of research to evaluate the relationship between the concentration of soluble fluoride present in toothpaste and the concentration found in saliva during and after brushing [Martinez-Mier et al, 2019], this study was done with Na 2 FPO 3 /Ca-CO 3 -based toothpaste. For this research, the brand of toothpaste was fixed (Table 1) and the variable under study was the concentration of TSF (ion FPO 3 2-+ ion F) in the toothpaste, which was obtained by standardized time of accelerated aging [Tabchoury and Cury, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…A toothpaste with Na 2 FPO 3 /Ca is usually formulated with 1,450 μg F/g, close to the total maximum fluoride (0.15%) allowed for most legislations of the world [MERCOSUL, 2002;European Union, 2008]. As Na 2 FPO 3 /Ca toothpaste may not maintain enough chemically soluble fluoride during its expiry time to be effective on caries reduction, it is necessary to have a methodology to estimate whether fluoride is bioavailable in the toothpaste formulation [Martinez-Mier et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toothpastes can be defined as creams or gels consisting of different chemical substances that facilitate the removal or disorganization of the dental biofilm and allow the supply of fluoride to act in the demineralization and remineralization of the dental substrate [15,16]. For this, the minimum According to results of the present study, this condition does not fit the toothpastes identified in the capital of Alagoas, since most toothpastes found for marketing have absence or low fluoride concentration, according to manufacturers' data.…”
Section: Discussionmentioning
confidence: 99%
“…. The participants of European Organization for Caries Research Workshop, which was held to discuss the issues related to the methodology for determination of potentially available fluoride in toothpastes, have emphasized the necessity of developing methods measuring fluoride bioavailability[28]. The development of techniques providing the assessment of free fluoride in mouthwashes is also required.…”
mentioning
confidence: 99%